Efficacy of supercritical carbon dioxide extracted dabai pulp oil and defatted dabai pulp in hypercholesterolemic sprague-dawley rats for cardiovascular health - Abdul Kadir, Noor Atiqah Aizan (2021)
Hypercholesterolemia is the hallmark of early cardiovascular diseases (CVDs), and CVDs are the primary cause of death globally. CVDs are attributed the causes of death for an estimated 17.9 million people each year (WHO, 2017). Canarium odontophyllum Miq. fruit (dabai) is a novel source for new healthy oil and nutraceuticals. The quality parameters of the supercritical carbon dioxide (SC-CO2) extracted dabai pulp oil (DPO) such as moisture and volatile content (MVC), free fatty acid content (FFA), iodine value (IV), peroxide value (PV), and fatty acids composition (FAC) were determined. This is the first study to examine the MVC, FFA, IV, and PV in SC-CO2 extracted DPO. The MVC of DPO was <0.001 ± 0.00%. Next, the FFA in DPO was 2.57 ± 0.03%, and the IV of DPO was 53.74 ± 0.08 g iodine/100 g oil. Meanwhile, the PV of DPO was 4.97 ± 0.00 mEq/kg. The main FAC of DPO was palmitic acid (41.56 ± 0.10 %), followed by oleic acid (39.37 ± 1.01 %) and linoleic (cis) acid (12.54 ± 1.03 %). DPO was characterised as SFA-rich oil due to its high SFA composition (47.65 ± 0.11 %). DPO also contained 0.01 ± 0.00 mg/100g oil of vitamin E (α-tocopherol) and syringic acid (2.11 ± 0.03 μg/ml). Meanwhile, the nutritional quality of defatted dabai pulp (DDP), such as total dietary fibre (TDF), total monomeric anthocyanin content (TAC), and antioxidant profile, were investigated. The amount of TDF in DDP was determined as 28.73 ± 1.82 g/100g. Whereas the amount of TAC in DDP was 523.3 ± 22.36 mg/100g. Further, HPLC analysis revealed that DDP contained gallic acid (8.73 ± 0.13 μg/ml), 4-hydroxybenzoic acid (61.46 ± 0.04 μg/ml), and syringic acid (89.87 ± 15.18 μg/ml). Additionally, antioxidant assay revealed that DDP showed excellent antioxidant profile; total phenolic content (TPC): 4.404 ± 0.09 mg GAE/g extract in DDP vs 0.118 ± 0.01 mg GAE/g extract in DPO, total flavonoid content (TFC): 2.699 ± 0.01 mg QE/g extract in DDP vs 0.093 ± 0.01 mg QE/g extract in DPO, and ferric ion reducing antioxidant power (FRAP): 5.743 ± 0.01 mM Fe/g extract in DDP vs 0.87 ± 0.01 mM Fe/g extract in DPO. As expected, incorporation of 2% DDP in experimental diet resulted in significantly higher TPC (3.969 ± 0.01 mg GAE/g of DDP vs 3.115 ± 0.00 mg GAE/g of DPO), TFC (1.072 ± 0.00 mg QE/g of DDP vs 0.796 ± 0.00 mg QE/g of DPO) and FRAP (11.197 ± 0.01 mM Fe/g of DDP vs 9.048 ± 0.01 mM Fe/g of DPO), as compared to 2% DPO (p<0.05). Further, the effectiveness of 2% of DPO and DDP was investigated against hypercholesterolemia elicited by a high-cholesterol diet in rats. Supplementation of 2% DDP and 2% DPO exerted beneficial effects against the high-cholesterol diet-fed rat. Nevertheless, results showed that 2% DDP was found to be more potent than 2% DPO in lowering TC (reduced by 35.37% in DDP vs 28.77% in DPO), LDL (reduced by 34% in DDP vs 16% in DPO), and HMG-CoA-r (reduced by 29.21% in DDP vs 18.81% in DPO) when compared with hypercholesterolemic rats (p<0.05). Rats treated with 2% DDP also showed higher improvement in TAS (higher by 7.26% against DPO), SOD (higher by 7.22% against DPO), and CAT (higher by 12.71% against DPO) when compared with hypercholesterolemic rats (p<0.05). Further, supplementation with 2% DDP resulted in the lowest CRP (reduced by 51.40% in DDP vs 29.90% in DPO), IL-6 (reduced by 31.20% in DDP vs 30.95% in DPO), and α-TNF (reduced by 36.12% in DDP vs 34.68% in DPO) levels compared to that of hypercholesterolemic rats (p<0.05). Meanwhile, liver histology and liver function test (AST and ALT) revealed that the 2% DDP and 2% of DPO showed no toxicological significance. The cholesterol-lowering effect of 2% DDP and 2% of DPO in hypercholesterolemic rats was investigated via the 1HNMR-based metabolomics approach. . Partial Least Squares- Discriminant Analysis (PLS-DA) was employed to investigate the anti-hypercholesterolemic effect of 2% DDP and 2% of DPO and to detect related potential biomarkers. A total of seven potential biomarkers were identified in the DPO treatment model, in which citrate had the highest variable importance in the projection (VIP) value (>3), followed by acetate, pyruvate, alanine, lysine, choline, and acetoacetate. Supplementation of 2% DPO showed a positive effect by upregulating citrate, yet the effect seen did not undergo significant changes compared with hypercholesterolemic rats (p>0.05). Meanwhile, a total of nine potential biomarkers were identified in the DDP treatment model, with citrate having the highest VIP value (> 3) followed by acetate, pyruvate, choline, cis-aconitate, acetoacetate, alanine, lysine, and methylmalonate. It turned out that 2% of DDP supplementation partially recovered the dysfunction in the metabolism induced by hypercholesterolemia via lipid metabolism. The biochemical analysis and metabolomic study results revealed that 2% of DDP has better hypolipidemic activities than 2% DPO. In conclusion, SC-CO2 extracted DDP ameliorates hypercholesterolemia by reducing TC, TG, LDL-C, and HMG-CoA-r levels. DDP also has a good effect against oxidative stress by increasing the antioxidant profile (TAS, SOD, and CAT) and reducing the inflammatory markers (CRP, α-TNF, and IL6) after 30 days of treatment. Hence, DDP is plausible to be developed as a novel source of bio-functional ingredients for the formulation of nutraceuticals. Meanwhile, the information on the quality parameters of DPO indicates the economic value of DPO to be used and commercialised as a new source of supplementary oil in the future.